Monitoring the quality of frozen-thawed venous segments using bioimpedance spectroscopy. (4th May 2020) - Amini, M; Niemi, E; Hisdal, J; Kalvøy, H; Tronstad, C; Scholz, H; Rosales, A; Martinsen, Ø G
Abstract: Objective : Storage at temperatures as low as −80 °C and below (cryopreservation) is considered a method for long-term preservation of cells and tissues, and especially blood vessel segments, which are to be used for clinical operations such as transplantation. However, the freezing and thawing processes themselves can induce injuries to the cells and tissue by damaging the structure and consequently functionality of the cryopreserved tissue. In addition, the level of damage is dependent on the rate of cooling and warming used during the freezing-thawing process. Current methods for monitoring the viability and integrity of cells and tissues after going through the freezing-thawing cycle are usually invasive and destructive to the cells and tissues. Therefore, employing monitoring methods which are not destructive to the cryopreserved tissues, such as bioimpedance measurement techniques, is necessary. In this study we aimed to design a bioimpedance measurement setup to detect changes in venous segments after freezing-thawing cycles in a noninvasive manner. Approach : A bioimpedance spectroscopy measurement technique with a two-electrode setup was employed to monitor ovine jugular vein segments after each cycle during a process of seven freezing-thawing cycles. Main results : The results demonstrated changes in the impedance spectra of the measured venous segments after each freezing-thawing cycle. Significance : This indicates that bioimpedance spectroscopy has the potential to be developed into a novel method for non-invasive and non-destructive monitoring of the viability of complex tissue after cryopreservation.